Pomegranate & fig - Ghani, Zaheda (Sydney, NSW : Hachette Australia, 2022)
The women arrive first, on an afternoon like any other, when Henna is safely enclosed behind her desk at school. They come to start a conversation that is both taboo and a normal part of life. A small, intimate group, precious stones decorate their necks and fingers, the sond, embroidery, on their pantaloons and translucent veils catches the afternoon light. Their eyebrows are groomed into elegant curves. They float on a cloud of perfume to Henna's family home.' A deeply moving novel about tradition, love, war and the sorrow & hope exile will bring. Tracing the lives of three young people, Henna, her brother Hamid, and a man who will become her husband, Rahim, this lyrical and evocative story reveals the political entanglements and family dynamics that are heightened and shattered by conflict. Taking us from the streets of Herat in the 1970s, invaded by Soviet forces, to India in the 1980s and then to the suburbs of Sydney, Pomegranate & Fig vividly illuminates the disruption, displacement and tragedy that war unleashes.
"From Afghanistan to Australia - a deeply moving novel about tradition, love, war and the sorrow and hope exile will bring."--Cover.
Keywords: Afghans -- Australia -- Fiction; Immigrants -- Fiction; Families -- Fiction; War stories; Interpersonal relations -- Fiction; Arranged marriage -- Fiction; Political violence -- Fiction; Domestic fiction; Australian fiction; Sydney (N.S.W.) -- Fiction; Herat (Afghanistan) -- Fiction; Herat (Afghanistan) -- Social conditions -- Fiction; Herat (Afghanistan) -- Social life and customs -- Fiction; Australian